Vista Eyes - Kurani, Prachit (Archives of Business Research, 2025)
This project aims at designing and developing an augmented reality application which will enable us to visualize and debug networks using an overlay of network information on the network devices. We propose an augmented reality technique to achieve this. Using 2D/3D image tracking offered by various libraries, the network devices can be identified by the system. Once the device is identified, it can be queried for various network parameters such as ping response time, number of open connections, amount of data transferred per second, number of network interfaces etc. The data can then be aggregated and analyzed. Once analysis is completed, visual representations of this data can be streamed to a VR device such as the Oculus/google cardboard. The oculus/cardboard then overlays this data on the network device itself.